2014
DOI: 10.1002/ejic.201402527
|View full text |Cite
|
Sign up to set email alerts
|

σ2P,O‐Hybrid Ligands: Synthesis of the First 4‐Hydroxy‐1,3‐benzazaphospholes by ortho‐Lithiation of m‐Amidophenyl Diethyl Phosphates

Abstract: The m-phosphorylanilides 2 are available from anilides 1 by the Atherton-Todd reaction; the selective ortho-lithiation of the oЈ-methyl-protected phosphorylpivalanilide 2b with tBuLi proceeded in high yield in the presence of ClSiMe 3 . The ortho-lithiation is followed by rapid 1,3-migration of the PO 3 Et 2 group to yield the phosphonoanilide cis/trans-3b. This compound mainly reacts with excess LiAlH 4 by reductive cyclization to form the 4-hydroxy-1H-1,3-benzazaphosphole 6. The lithiation of the oЈ-unprotec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Reduction of 41 with excess LiAlH 4 did not lead to an OHÀ and NH-functional primary phosphane but, by intramolecular attack of PH 2 or PHLi at the adjacent N=C(OLi)tBu group, to a 1H-1,3-benzazaphosphole, the so far only example of a P=C-NR-heterocycle with OH-group in o-position to the (relatively π-electron rich) σ 2 -P-atom. [106]…”
Section: O-hydroxyarylphosphanes Via Cà P Bond Formation With O-oc-di...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of 41 with excess LiAlH 4 did not lead to an OHÀ and NH-functional primary phosphane but, by intramolecular attack of PH 2 or PHLi at the adjacent N=C(OLi)tBu group, to a 1H-1,3-benzazaphosphole, the so far only example of a P=C-NR-heterocycle with OH-group in o-position to the (relatively π-electron rich) σ 2 -P-atom. [106]…”
Section: O-hydroxyarylphosphanes Via Cà P Bond Formation With O-oc-di...mentioning
confidence: 99%
“…Another type of C,O‐dilithium reagents ( 39 ) is formed by reaction of N ‐acylanilides with t BuLi in THF (−20 °C), including directed o ‐lithiation and lithiation of the NHC(O) fragment to a delocalized (NCO)Li group. Subsequent C−P coupling with a ) Cl n PPh 3‐n or b ) an o ‐O‐bound PO 3 Et 2 group via 1,3‐anionic O−C rearrangement was used for the synthesis of related o ‐phosphanylaniline derivatives 40 [105] or of compound 41 with an additional o ’−OH group [106] (Scheme 11). Reduction of 41 with excess LiAlH 4 did not lead to an OH− and NH‐functional primary phosphane but, by intramolecular attack of PH 2 or PHLi at the adjacent N=C(OLi) t Bu group, to a 1 H ‐1,3‐benzazaphosphole, the so far only example of a P=C‐NR‐heterocycle with OH‐group in o ‐position to the (relatively π‐electron rich) σ 2 ‐P‐atom [106] …”
Section: Routes To 2‐hydroxyarylphosphanesmentioning
confidence: 99%
“…4‐Methoxy‐ and 4‐hydroxy‐2‐ tert ‐butyl‐1,3‐benzazaphospholes 15a and 15b , respectively, with +M donor groups in the o ‐position to σ 2 P, were obtained through phosphonylation of o ‐lithiated pivalamides, generated in directed ortholithiation steps, and subsequent reductive cyclization (Scheme ) 37,41. In the second case the phosphonylation proceeded with carbanionic O–C migration of the P(O)(OEt) 2 group and was interfered with by side reactions induced by the lithium‐pivalamide function unless this was trapped by chlorotrimethylsilane, added before the bulky lithiation reagent 41. Other functional groups were introduced by NH‐ or 2‐CH‐lithiation and subsequent electrophilic substitution (see below).…”
Section: Recent Syntheses and New Types Of Electron‐rich Heterophomentioning
confidence: 99%
“…47 While numerous 1 H -1,3-benzazaphospholes ( R-BAP ) have been reported, no significant photoluminescence studies have appeared. 48–55 However, we have shown that a benzazaphosphole ( F , Chart 1) adhered to carbazole (a common fluorophore) can display significant luminescence distinct from carbazole. 56 The development of other luminescent materials featuring σ 2 ,λ 3 -phosphorus is rapidly expanding, as recent examples G–J illustrate in Chart 1.…”
Section: Introductionmentioning
confidence: 99%